EFEKTIFITAS PENERAPAN MODEL PEMBELAJARAN KOOPERATIF DALAM PEMBELAJARAN KALKULUS - Suparni Suparni (IAIN PADANGSIDIMPUAN, 2015)
The choice of method / model appropriate learning, according to the material / lesson material that will be given to students is the right step in the quest to improve the quality of learning outcomes. This study aims to improve the activity and student learning outcomes through the application of the Jigsaw cooperative learning. The hypothesis of this study is the application of the Jigsaw cooperative learning in the learning process can improve the activity and student learning outcomes. This research is a class action (Action Research), conducted on 46 people MHS Prodi STAIN Padangsidimpuan TMM. Data were collected through observation sheet and achievement test. The results showed that the average value of student learning outcomes at the end of the study reach 81.1 and the percentage of positive student learning activity has been demonstrated in both criteria.